IMPLEMENTASI METODE ARMA DALAM PERAMALAN INFLASI PROVINSI BANTEN - Miftahul Huda; Ratu Nihayah Nur Azizah; Ajeng Nur Setyana (LPPM Universitas Bina Bangsa, 2023)
Inflation is one of indicators of economic stability in a region. Banten Province experiences fluctuating inflation developments from year to year. This fluctuation can be influenced by neighboring provinces such as Lampung and DKI Jakarta Province. Furthermore, inflation calculations in Banten are based on the Consumer Price Index (CPI) values from three major cities in Banten: Tangerang City, Cilegon City, and Serang City. This means that inflation value can depict the cost of living movement over a specific period. Forecasting consumer prices, including food, drinks, tobacco, health, education, and others, is necessary to help consumers plan their finances wisely for the future. One method suitable for this forecasting is ARMA(p,q). The ARMA method is used for forecasting based on time series data for stationary data patterns. ARMA model was conducted using the Box-Jenkins method, involving steps of identification model, diagnostic model, and forecasting. The objective of this research is to forecast the inflation value at the end of 2023 using the ARMA method with inflation data from January 2018 to August 2023. This research resulted in an ARMA(1,1) model as the forecasting with MSE=0.0720176. The forecast for September to December 2023 indicates a significant increase in inflation, with inflation values of 0.211182, 0.264935, 0.233054, and 0.251963, respectively